PERLINDUNGAN HUKUM TERHADAP LESSEE DI MASA PANDEMI COVID-19 - Rachel Natalie Grace, (2022)
COVID-19 pandemic since 2020 has an impact on the lives of Indonesian people, including financial services industry. Lessee who are in a financing loan have difficulty paying their loans, so the Financial Services Authority (OJK) issued a policy of providing national economic stimulus, POJK Number 11/PJOK.03/2020 for bank and POJK Number 14/POJK.05/2020 (POJK 14/2020) for the non-bank financial services like leasing. However, POJK Number 14/2020 amended in POJK Number 58/POJK.05/2020 (POJK 58/2020) is considered not yet able to provide legal protection for lessee because the freedom for leasing companies to make their affected debtor criteria and restructuring scheme. The problems to be discussed are how the legal consequences and legal protection for lessee as it isn't regulated in POJK 14/2020 amended in POJK 58/2020. The method used is normative legal research, by examining existing regulations. The conclusion from this research is that there is legal ambiguity where POJK Number 14/2020, so that lessee should be protected by law, namely Indonesian Civil Law, Law of the Republic of Indonesia Number 8 of 1999 on Consumer Protection, Law of the Republic of Indonesia Number 21 of 2011 concerning the Financial Services Authority (OJK), POJK No. 1/POJK.07/2013, complaints settlements through BPKN, Institutions for Alternative Dispute Resolution for the Financial Services Sector (LAPS-SJK), and litigation. To ensure legal certainty and consumer protection, OJK should make new POJK related to debtor criteria and restructuring schemes, optimize LAPS-SJK, and oversee the implementation of restructuring for debtors that are truly affected by the pandemic.